Thyroid Disorders in Patients Treated with Dimethyl Fumarate for Multiple Sclerosis: A Retrospective Observational Study - Cédric O. Renaud; Panos G. Ziros; Amandine Mathias; Caroline Pot; Gerasimos P. Sykiotis (MDPI AG, 2022)
Background: Dimethyl fumarate (DMF), a drug used for the treatment of multiple sclerosis (MS) and psoriasis, has been shown to activate the Keap1/Nrf2 antioxidant response. Nrf2 exerts pleiotropic roles in the thyroid gland; among others, single nucleotide polymorphisms (SNPs) in the gene encoding Nrf2 modulate the risk of Hashimoto's thyroiditis (HT), suggesting that pharmacological activation of Nrf2 might also be protective. However, a patient with acute exacerbation of HT after starting DMF for MS was recently reported, raising questions about the thyroidal safety of Nrf2 activators. Methods: In a retrospective observational study, we investigated the prevalence and incidence of thyroid disorders (TD) among 163 patients with MS treated with DMF. Results: Only 7/163 patients (4.3%) were diagnosed with functional TD; most (5/163, 3.0%) were diagnosed before DMF treatment. Functional TD were diagnosed under or after DMF in only 2 patients (1.2%). Under DMF, one patient developed transient mild hypothyroidism with negative thyroid autoantibodies. After DMF discontinuation, another patient developed hyperthyroidism due to Graves' disease. No patient developed thyroid structural disease under or after DMF. Conclusions: The very low incidence of functional TD indicates an overall very good thyroid tolerance of DMF, arguing against screening for TD in MS patients considered for or treated with DMF, and supporting the further study of Nrf2 activators for the prevention and treatment of TD.